Parental and individual determinants of dental trust in children: a path analysis of a conceptual model - Betul Taskaya; Burak Buldur (BMC Oral Health)
Abstract Background Understanding the interactions among predictors of dental trust in children is important for designing effective interventions in pediatric dental care. Aim This study aimed to develop and validate a conceptual model to evaluate factors influencing dental trust in children. Design This cross-sectional study included 267 parent-child dyads. Data collection tools included a sociodemographic data form, the Turkish Oral Health Literacy Assessment Task (TOHLAT-P), the Dental Trust Scale (DTS), the Children’s Fear Survey Schedule-Dental Subscale (CFSS-DS), and the Early Childhood Oral Health Impact Scale (ECOHIS). The conceptual model explored the factors influencing dental trust in children by incorporating endogenous and exogenous variables. Path analysis was conducted to test model fit. Results Dental trust was significantly associated with parental oral health literacy (β = −0.20; P < 0.001), dental anxiety (β = −0.18; P < 0.001), and oral health-related quality of life (β = −0.15; P < 0.001). The path analysis confirmed the validity of the proposed model, showing significant pathways between these variables and dental trust in children. Conclusions This study presents a validated model illustrating the relationships between parental and child-related factors and dental trust in children. These findings underscore the importance of addressing these factors in clinical strategies to enhance dental trust and improve pediatric dental outcomes.